The economics of influencers and social media stardom - Sophia Gänßle; Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2023)
This chapter provides an overview of the economics of influencers and social media stardom. It provides the state-of-research regarding success factors, revenue and payment models, social media platforms and ecosystems, and welfare effects. It describes the role of social media content providers within the media industries and explores the differences and similarities of this new innovative element in media markets compared to its more traditional counterparts (traditional stars and traditional media industries).
Keywords: L82; Z10; L13; L15; L86; D43; D83; F23; M21; D91; L26; 330; social media; superstars; influencer; platforms; stardom; content producers; YouTube; Instagram; TikTok; gatekeepers